Manajemen Kurikulum Terpadu Berbasis Multiple Intellegences di Pondok Pesantren - Akhmad Sirojuddin; Ashlahuddin Ashlahuddin; Andika Aprilianto (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2022)
The purpose of this article is to describe the implementation of an integrated curriculum based on multiple intelligences at the Riyadlul Jannah Islamic Boarding School, Mojokerto. This article uses a qualitative approach, in which this research was conducted at the Riyadlul Jannah Islamic boarding school, Mojokerto. Meanwhile, as an informant to find out what the researchers studied were the management coordinator, the student coordinator and the teachers. The data collection techniques in this study are in-depth interviews, observations or observations of educational activities, and documentation. And for the data validity technique, which includes source triangulation and data triangulation techniques. The results of this article are, namely: the history of the Riyadlul Jannah Islamic boarding school in Mojokerto, synchronization or integration between general education and Islamic boarding school education to support each other for a complete education, starting from the planning of an integrated curriculum which includes planning superior education programs and suggestions for infrastructure in the implementation of the practice. in-depth, integrated curriculum implementers in implementing each program or preparing natural resources, and integrated curriculum supervision which is carried out to become a benchmark in the achievement of students who are diverse or have multiple intelligences, and then can make development policies in future planning.